Nicotinamide mononucleotide boosts the development of bovine oocyte by enhancing mitochondrial function and reducing chromosome lagging - Shu Hashimoto; Udayanga Gamage; Yuki Inoue; Hisataka Iwata; Yoshiharu Morimoto (Scientific Reports)
Abstract Nicotinamide adenine dinucleotide (NAD(H)) and its metabolites function as crucial regulators of physiological processes, allowing cells to adapt to environmental changes such as nutritional deficiencies, genotoxic factors, disruptions in circadian rhythms, infections, inflammation, and exogenous substances. Here, we investigated whether elevated NAD(H) levels in oocytes enhance their quality and improve developmental competence following in vitro fertilization (IVF). Bovine cumulus-oocyte complexes (COCs) were matured in a culture medium supplemented with 0–100 μM nicotinamide mononucleotide (NMN), a precursor of NAD(H). The addition of NMN caused an increase in intracellular NAD(H) and nicotinamide adenine dinucleotide phosphate levels, leading to enhanced competence for development to the blastocyst stage after IVF. The increase in intracellular NAD(H) levels led to changes in the expression of mitochondria function-related genes. As a result, NMN supplementation increased the ratio of MitoTracker Orange fluorescence to nonyl acridine orange fluorescence, as well as adenosine triphosphate levels, while decreasing reactive oxygen species levels in the oocytes. NMN also lowered chromosome lagging during anaphase. These results suggest that increased NAD(H) levels in oocytes following NMN treatment enhances post-fertilization developmental competence through improved mitochondrial function.